Socioeconomic and environmental impact of the implementation of renewable energy: an analysis from the neutrosophic PESTSWOT - Alvarez-Bernuy, Silvia M. (2025)
The Mantaro Valley in Peru is an inter-Andean River valley, through which the Mantaro River passes. Approximately a population of one million inhabitants live here. Currently, the damage caused by the use of non-renewable energy sources is very evident, both to the environment and to the local economy, which will become unsustainable in the future. That is why we want to critically study the implementation of renewable energy projects that support the generation of electricity and other types of energy in this area. However, this has some positive and negative elements. In this paper, we apply a PEST-SWOT analysis to evaluate the balance of each of these aspects. Furthermore, we use an evaluation in the form of single-valued neutrosophic numbers, which allow us to capture the uncertainty and indeterminacy in this decision-making problem.